Recent results from the G0 experiment - Roos P.; Roche J.; Ramsay W.D.; Quinn B.; Poelker M.; Pitt M.L.; Pillot P.; Phillips S.K.; Pate S.F.; Papavassiliou V.; Page S.A.; van Oers W.T.H.; et al. (EPJ Web of Conferences, 2010)
We have measured parity violating asymmetries in elastic electron-proton and quasi-elastic electrondeuteron scattering at backward electron angle. These measurements have been done at two momentum transfers : Q2 = 0.22 and 0.63 (GeV/c)2 . Together with our previous forward angle measurement [1], we can extract strange quark contributions to the electromagnetic form factors of the nucleon, as well as nucleon axial form factor coming from the neutral weak interaction. The results indicate a strange quark magnetic contribution close to zero at these Q2 , and a possible non zero strange quark electric contribution for the high Q2 . The ﬁrst Q2 behavior measurement of the nucleon axial form factor in elastic electron scattering shows a good agreement with radiative corrections calculated at Q2 = 0 and with a dipole form using the axial mass determined in neutrino scattering.